2020
DOI: 10.3390/ijgi9040273
|View full text |Cite
|
Sign up to set email alerts
|

Testing a Comprehensive Volcanic Risk Assessment of Tenerife by Volcanic Hazard Simulations and Social Vulnerability Analysis

Abstract: Volcanic activity remains highly detrimental to populations, property and activities in the range of its products. In order to reduce the impact of volcanic processes and products, it is critically important to conduct comprehensive volcanic risk assessments on volcanically active areas. This study tests a volcanic risk assessment methodology based on numerical simulations of volcanic hazards and quantitative analysis of social vulnerability in the Spanish island of Tenerife, a well-known tourist destination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…where X i and Y i are the original and normalized values of the measures respectively and Max i and Min i are the maximum and minimum values of the measures, respectively. This method was used in previous studies for normalizing different measures [22,52]. As Yang et al [53] have shown that greenness is both a positive contributor and the largest contributor to the urban eco-environment quality, the greenness measure was treated as a benchmark here and its correlation with the other measures helped to determine the nature of their contributions to the urban eco-environment quality.…”
Section: Normalization Of the Measuresmentioning
confidence: 99%
“…where X i and Y i are the original and normalized values of the measures respectively and Max i and Min i are the maximum and minimum values of the measures, respectively. This method was used in previous studies for normalizing different measures [22,52]. As Yang et al [53] have shown that greenness is both a positive contributor and the largest contributor to the urban eco-environment quality, the greenness measure was treated as a benchmark here and its correlation with the other measures helped to determine the nature of their contributions to the urban eco-environment quality.…”
Section: Normalization Of the Measuresmentioning
confidence: 99%
“…Random forest (RF) was selected for urban land use classification in this study as it is a superior classifier in producing accurate results for various purposes, e.g. mapping lava flow of different age [47], regional land use [48], urban vegetation types [49], and volcanic risk assessment [50]. The number of trees (ntree) and random features (mtry) are two important parameters in RF classification and usually determined by trial and error [51].…”
Section: Random Forest Classificationmentioning
confidence: 99%
“…In the early stages, the vulnerability concept was mainly applied to the assessment of natural disasters such as floods and droughts or ecosystems such as forests and coasts [2][3][4][5]. With the gradual integration and penetration of the natural and social systems, the interaction between the natural environment and human social activities has become increasingly obvious [6], and the relevant research on vulnerability has gradually extended to the social and economic fields [7,8]. As one of the important components of the concept and connotation of vulnerability, economic vulnerability refers to the bearing capacity of the regional economy due to the impact of unexpected events in the process of 2 of 21 development [9,10].…”
Section: Introductionmentioning
confidence: 99%